(untitled) - Khaldoun Mousa Aldiabat; Enam Alsrayheen; Carole-Lynne Le Navenec; Catherine Aquino-Russell; Mohammad Al Qadire (University of Ostrava, 2021)
Aim: This study aimed to investigate the experience of retirement for retired nursing professors. Design: The descriptive phenomenological qualitative method, developed by Giorgi, was used to conduct this study, through the lens of Continuity Theory and Carper's Ways of Knowing Theory. Methods: Data were collected from four eligible participants in the form of written descriptions e-mailed to the researchers and analyzed using Giorgi's analysis-synthesis process. Results: The results showed that retired nursing professors felt satisfied with what they had achieved over their careers. They experienced a positive and rewarding life post-retirement and had positive perceptions of many aspects of their retirement. Conclusion: The retired nursing professors continued with many pre-retirement activities and maintained productivity. They used their past and new knowledge to shape their daily life experiences in ways that enhanced their own well-being and quality of family and community connections. Their continued involvement in organizations post-retirement included many academic and professional activities such as presenting at conferences, supervising students, reviewing articles, and volunteering in other scholarly activities.